Transcriptomics Reveals the Mevalonate and Cholesterol Pathways Blocking as Part of the Bacterial Cyclodipeptides Cytotoxic Effects in HeLa Cells of Human Cervix Adenocarcinoma - Lázaro-Mixteco, Pedro E.; González-Coronel, José M.; Hernández-Padilla, Laura; Martínez-Alcantar, Lorena; Martínez-Carranza, Enrique; López-Bucio, Jesús Salvador; Guevara-García, Ángel A.; Campos-García, Jesús (Frontiers in Oncology, 2022)
The incidence of human cervix adenocarcinoma (CC) caused by papillomavirus genome integration into the host chromosome is the third most common cancer among women. Bacterial cyclodipeptides (CDPs) exert cytotoxic effects in human cervical cancer HeLa cells, primarily by blocking the PI3K/Akt/mTOR pathway, but downstream responses comprising gene expression remain unstudied. Seeking to understand the cytotoxic and anti-proliferative effects of CDPs in HeLa cells, a global RNA-Seq analysis was performed. This strategy permitted the identification of 151 differentially expressed genes (DEGs), which were either up- or down-regulated in response to CDPs exposure. Database analysis, including Gene Ontology (COG), and the Kyoto Encyclopedia of Genes and Genomes (KEGG), revealed differential gene expression on cancer transduction signals, and metabolic pathways, for which, expression profiles were modified by the CDPs exposure. Bioinformatics confirmed the impact of CDPs in the differential expression of genes from signal transduction pathways such as PI3K-Akt, mTOR, FoxO, Wnt, MAPK, P53, TGF-, Notch, apoptosis, EMT, and CSC. Additionally, the CDPs exposure modified the expression of cancer-related transcription factors involved in the regulation of processes such as epigenetics, DNA splicing, and damage response. Interestingly, the transcriptomic analysis revealed the participation of genes of the mevalonate and cholesterol biosynthesis pathways; in agreement with this observation, total cholesterol diminished, confirming the blockage of the cholesterol synthesis by the exposure of HeLa cells to CDPs. Interestingly, the expression of some genes of the mevalonate and cholesterol synthesis such as HMGS1, HMGCR, IDI1, SQLE, MSMO1, SREBF1, and SOAT1 was up-regulated by CDPs exposure. Accordingly, metabolites of the mevalonate pathway were accumulated in cultures treated with CDPs. This finding further suggests that the metabolism of cholesterol is crucial for the occurrence of CC, and the blockade of the sterol synthesis as an anti-proliferative mechanism of the bacterial CDPs, represents a reasonable chemotherapeutic drug target to explore. Our transcriptomic study supports the anti-neoplastic effects of bacterial CDPs in HeLa cells shown previously, providing new insights into the transduction signals, transcription factors, and metabolic pathways, such as mevalonate and cholesterol that are impacted by the CDPs and highlights its potential as anti-neoplastic drugs.